Visualization of the cancer cell cycle by tissue‐clearing technology using the Fucci reporter system. Issue 9 (7th July 2021) - Takahashi, Kei; Tanabe, Ryo; Ehata, Shogo; Kubota, Shimpei I.; Morishita, Yasuyuki; Ueda, Hiroki R.; Miyazono, Kohei
Abstract: Tissue‐clearing technology is an emerging imaging technique currently utilized not only in neuroscience research but also in cancer research. In our previous reports, tissue‐clearing methods were used for the detection of metastatic tumors. Here, we showed that the cell cycles of primary and metastatic tumors were visualized by tissue‐clearing methods using a reporter system. First, we established cancer cell lines stably expressing fluorescent ubiquitination‐based cell cycle indicator (Fucci) reporter with widely used cancer cell lines A549 and 4T1. Fluorescence patterns of the Fucci reporter were investigated in various tumor inoculation models in mice. Interestingly, fluorescence patterns of the Fucci reporter of tumor colonies were different between various organs, and even among colonies in the same organs. The effects of antitumor drugs were also evaluated using these Fucci reporter cells. Of the three antitumor drugs studied, 5‐fluorouracil treatment on 4T1‐Fucci cells resulted in characteristic fluorescent patterns by the induction of G2 /M arrest both in vitro and in vivo. Thus, the combination of a tissue‐clearing method with the Fucci reporter is useful for analyzing the mechanisms of cancer metastasis and drug resistance. Abstract : Monitoring the Fucci patterns in vivo with 4T1‐Fucci cells. A, B, 3D and 2D images of 4T1 cells inoculated orthotopically into the mammary fat‐pad. C, 3D and 2D images of 4T1‐Fucci cells in experimental lung metastasis.